FASILITAS PADA EKOWISATA DANAU NAGA SAKTI DI KABUPATEN SIAK SRI INDRAPURA RIAU - Yulia Citra Siregar; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The phenomenon of adventure in nature forest and open nature gives the feel of different tours. A natural adventure may be hard to find right now. The natural area of river, lake, swamp, peat ecosystem, upstream or river eatuary can also be used ecotourism. Siak sri Indrapura is known for the historical tourism in fact keeps the natural beauty of interest to visit and has been known to to have natural wealth. On of them is lake naga sakti ecotourism that was developed into a tourist attraction in Siak. The availability of facilities in area of tourism is a readiness of a menas to be operated and can provide comfort to tourists.This study aims to determine: (1) To know the facilities in the lake Naga Sakti ecotourism. (2) Factors that affect the provision of facilities in the lake Naga Sakti ecotourism. In this study the research method that I use is a qualitative method with descriptive approach. Technique of collecting data in this research use observation, interview and documentation.Based on research that has been done, the existing facilities in the ecotourism of the lake Naga sakti is not adequate. This is because there are still facilities that have not functioned maximally and received less attention from the manager of lake Naga Sakti ecotourismKeywords: Facilities, Ecotourism, Tourism Object